Knowledge and attitudes of pain Management among nursing Students In School of Health Sciences, USM - Sze, Chai Li (PPSP, Universiti Sains Malaysia, 2007)
Lack of knowledge and negative attitudes of nurses towards pain management had been linked to under treatment of pain in hospitalized patients. Students must be equipped with knowledge, attitudes, and skills in an effort to provide future nurses with adequate knowledge and attitudes of pain management, in order to decrease the suffering of hospitalized patients. Unfortunately, the problems of lacking adequate information and positive attitudes towards pain management among students have been documented. Objective: To determine the current pain management knowledge and attitudes of USM nursing students, compare the level of pain management knowledge and attitudes between second year, third year, and fourth year nursing students, and determine the relationship of personal previous experience of pain with the knowledge and attitudes of nursing students' regarding pain management. Methodology: Cross-sectional and comparative in designs, this descriptive study included second, third and fourth year degree nursing students (N=l07). Knowledge and attitudes were examined via a questionnaire based on McCaffery and Ferrell's NKASRP with reliability alpha 0. 76. Result: On average, all nursing students scored 55.1 %, demonstrating significant knowledge and attitudes deficiencies regarding pain management. Results from this study revealed that no significant difference of knowledge and attitudes in pain management lX among second year, third year, and final year students. Result also revealed that previous personal experience of pain did not made any contribution to knowledge and attitudes. Conclusion: Undergraduate nursing curricula need to be evaluated from a number of perspectives to improve the students' attitudes and knowledge of pain management. Development of nursing program in pain management is urgently needed to increase and disseminate pain education and knowledge.